A big leap for Universiti Malaysia Pahang - Ong, Han Sean (2018)
KUANTAN: Universiti Malaysia Pahang (UMP) has made a noteworthy increase in the 2019 QS Asian University Rankings by a leap of 100 places to the 188 spot from the 251-300 range in just six years.